JUSTIFIKASI INTERVENSI INTERNASIONAL DALAM KONFLIK SUATU NEGARA - Andaru Satnyoto (Kajian Asia Pasifik, 2017)
Conflict among states or interstate conflict is still part of the important concern in the politics and international relations. International attention is becoming stronger along with the shift view of international society regarding the intervention justification to reduce the conflict. Realist and moralist perspective are changed by cosmopolitan one since the individual interest and security are more important rather than the will to maintain the state security including motives of sphere of influence and maintaining group stability and balance of power. This post-cold war phenomenon on the intervention justification tends to be conducted in the multilateral way and it is urged by humanity reasons – that is why it is called humanitarian intervention -- rather than political and state security reasons. The significance of intervention in the international relations is debatable issue since it involves various matter like legalistic language/term, various interests and international opinion. Keywords: intervention, justification of intervention, humanitarian intervention, cosmopolitan perspective Abstrak Konflik antar negara (inter-state conflict) menjadi perhatian penting dalam politik dan hubungan internasional. Perhatian internasional menjadi semakin kuat dengan adanya pergeseran pandangan masyarakat internasional terkait justifikasi intervensi untuk meredam konflik. Perspektif realis dan moralis digeser oleh (perspektif kosmopolitan) mengingat kepentingan dan keamanan individu lebih penting daripada keinginan untuk mempertahankan keamanan negara termasuk motif-motif lingkungan pengaruh, mempertahankan stabilitas kelompok dan perimbangan kekuasaan. Justifikasi intervensi yang merupakan fenomena perang dingin cenderung dilaksanakan dengan cara multilateral dan didorong oleh alasan-alasan kemanusiaan – itulah mengapa disebut dengan intervensi kemanusiaan (humanitarian intervention) – daripada alasan politik dan keamanan negara. Signifikansi intervensi dalam hubungan internasional merupakan isu yang diperdebatkan karena melibatkan berbagai hal seperti pengertian legalistik, berbagai kepentingan dan opini internasional. Kata kunci: intervensi, justifikasi intervensi, intervensi kemanusiaan, perspektif kosmopolitan